Membrane Restructuring Events during the Enzymatic Generation of Ceramides with Very Long-Chain Polyunsaturated Fatty Acids - Peñalva, Daniel Alejandro (2018)
In rat sperm heads, sphingomyelin (SM) species that contain very long-chain polyunsaturated fatty acid (V-SM) become ceramides (V-Cer) after inducing in vitro the acrosomal reaction. The reason for such a specific location of this conversion, catalyzed by a sphingomyelinase (SMase), has received little investigation so far. Here, the effects of SMase were compared in unilamellar vesicles (large unilamellar vesicles (LUVs), giant unilamellar vesicles (GUVs)) containing phosphatidylcholine, and either V-SM or a palmitate-rich SM (P-SM). In uniformly sized LUVs at 37 °C, more V-Cer was generated and more rapidly than P-Cer. Nephelometry and dynamic light scattering showed that LUVs tended to form large lipid particles more intensely, and Förster resonance energy transfer (FRET) increases suggested that lateral lipid mixing was more marked when V-Cer rather than P-Cer was produced. As reported by 6-dodecanoyl-2-dimethyl-aminopnaphthalene (Laurdan) and 1,6-diphenyl-1,3,5,-hexatriene (DPH), the production of V-Cer resulted in higher and faster restriction in lipid mobility than that of P-Cer, implying a stronger increase in membrane dehydration and microviscosity. Moreover, DPH anisotropy suggested a higher solubility of V-Cer than that of P-Cer in the liquid-disordered phase. At room temperature, liquid-condensed lateral domains appeared in P-SM- but not in V-SM-containing GUVs. The former maintained their size while losing their contents gradually during SMase action, whereas the latter became permeable earlier and reduced their size in few minutes until suddenly collapsing. The fast and potent generation of V-Cer may contribute to the membrane restructuring events that occur on the acrosome-reacted sperm head.